Penerapan Metode Diskusi Untuk Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Tematik Kelas V SD - Lia, Shelia Pramesti; Setyawan, Agung (CAHAYA: Journal of Research on Science Education, 2023)
The background of this research is because most of the fifth grade elementary school students in this thematic learning feel that the learning that is being carried out tends to be monotonous and the children become bored and lack enthusiasm in learning. This research aims to increase the understanding of fifth grade students at SD Negeri Karangasem in increasing enthusiasm in learning especially in thematic subjects. The subjects of this study were 11 fifth grade students at SDN Karangasem. Instruments in this study were interviews, observations, tests, documentation, and field notes. The results of the study prove that there is a significant increase when researchers use the discussion method. When the implementation of cycle I obtained greater or equal good ethics, only 10% with a number of students of 2 students from a total of 11 students. Then in cycle III the increase in student learning motivation has obtained indicators of success, because the number of students who obtain is greater or as good as 90% with a total of 11 students.